2020
DOI: 10.15694/mep.2020.000055.1
|View full text |Cite
|
Sign up to set email alerts
|

Does an incremental approach to implementing programmatic assessment work? Reflections on the change process

Abstract: In 2017, the School of Medicine (Fremantle) of the University of Notre Dame Australia began moving towards programmatic assessment. Programmatic assessment seeks to achieve robust assessment validity through the assessment of a large number of low-stakes activities or data points. These data points exemplify assessment as learning by valuing feedback, discussion and reflection, ultimately leading to deeper student engagement without compromising credible decision-making on student progress. The School adopted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, there could also be principles that are easier to implement or address a certain need in a particular organisation or context, which might create effective hybrids. There are examples of such hybrid or incremental approaches (Bala et al 2020;Bate et al 2020) and McDowell reported on the implementation of programme focused assessment in a number of Higher Education institutes in the United Kingdom, which featured horizontal integrative assessment across stages/years of a programme (McDowell 2012). More research on the effects of various implementations of programmatic assessment on outcomes such as learning behaviour and decision making is definitely needed.…”
Section: Recommendations For Future Workmentioning
confidence: 99%
“…However, there could also be principles that are easier to implement or address a certain need in a particular organisation or context, which might create effective hybrids. There are examples of such hybrid or incremental approaches (Bala et al 2020;Bate et al 2020) and McDowell reported on the implementation of programme focused assessment in a number of Higher Education institutes in the United Kingdom, which featured horizontal integrative assessment across stages/years of a programme (McDowell 2012). More research on the effects of various implementations of programmatic assessment on outcomes such as learning behaviour and decision making is definitely needed.…”
Section: Recommendations For Future Workmentioning
confidence: 99%
“…Yet early adopters have encountered challenges such as stakeholder resistance (Baartman et al, 2023;Jamieson et al, 2022;Schut et al, 2021) and design choice dilemmas when applying theoretical principles to authentic practice (Baartman et al, 2022;Schut et al, 2021). The continued perception, or use, of summative assessments has proven di cult to shake and undermines assessment's intended learning function (Baartman et al, 2023;Bate et al, 2020;Schut et al, 2021). There is propensity for overassessment which can burden all stakeholders (Bate et al, 2020;Schut et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The continued perception, or use, of summative assessments has proven di cult to shake and undermines assessment's intended learning function (Baartman et al, 2023;Bate et al, 2020;Schut et al, 2021). There is propensity for overassessment which can burden all stakeholders (Bate et al, 2020;Schut et al, 2021). These implementation challenges may impede widespread adoption and hinder attainment of desired outcomes (Ryan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of ‘data point’ applied in the PA approach refers to information on student performance that is collected from a single assessment method [ 8 , 12 ]. Single data points are used in formative assessment to provide constructive feedback, which guides learning [ 13 , 16 ]. The progressive accumulation of multiple data points becomes the premise of pass-or-fail decisions reached by a group of assessment experts [ 3 ].…”
Section: Introductionmentioning
confidence: 99%